The Same is Not the Same: Device Effect during Bipolar Radiofrequency Ablation of Atrial Fibrillation - Niemann, Bernd; Dominik, Elisabeth; Rohrbach, Susanne; Grieshaber, Philippe; Roth, Peter; Böning, Andreas (The Thoracic and Cardiovascular Surgeon, 2019)
Background Different ablation devices deliver the same type of energy but use individual control mechanisms to estimate efficacy. We compared patient outcome after the application of radiofrequency ablation systems, using temperature- or resistance-control in paroxysmal and persistent atrial fibrillation (AF).Methods This is an unselected all-comers study. Patients underwent standardized left atrial (paroxysmal atrial fibrillation, [PAF] n = 31) or biatrial ablation (persistent atrial fibrillation [persAF] n = 61) with bipolar RF from October 2010 to June 2013. Patients with left atrial dilatation (up to 57 mm), reduced left ventricular (LV) function, and elderly were included. We used resistance-controlled (RC) or temperature-controlled (TC) devices. We amputated atrial appendices and checked intraoperatively for completeness of pulmonary vein exit block. All patients received implantable loop recorders. Follow-up interval was every 6 months. Antiarrhythmic medical treatment endured up to month 6.Results We reached 100% freedom from atrial fibrillation (FAF) in PAF. In perAF 19% of the RC but 82% of the TC patients reached FAF (12 months; p < 0.05). TC patients exhibited higher creatine kinase-muscle/brain (CK-MB) peak values. In persAF, CK-MB-levels correlated to FAF. No and no mortality (30 days) was evident. Twelve-month mortality did not correlate to AF type, AF duration, LV dimension, or function and age. Prolonged need of oral anticoagulants was 90.1% (RC) and 4.5% (TC).Conclusion In patients with persAF undergoing RF ablation, TC reached higher FAF than RC. Medical devices are not “the same” regarding effectiveness even if used according to manufacturer's instructions. Thus, putative application of “the same” energy is not always “the same” efficacy.
Keywords: atrial fibrillation; surgery; techniques